Política pública de uso e ocupação do solo da margem direita do Rio Negro, princípio da precaução e sustentabilidade sociambiental: uma articulação possÍvel? - Nogueira, Marcondes Gil (2012)
Discusses a research process that aims to analyze the public policy of use and occupation of the right bank of the Rio Negro from the principle of precaution and the social and environmental sustainability. The specific objectives are: to characterize the socio-economic, cultural and geopolitical organization of the municipality of Iranduba, emphasizing the key social and environmental problems exist, identify the general guidelines contained in the plan of action for use and occupation of the right bank of the Rio Negro, focusing expected results for the Iranduba Map and the expected results in terms of use and occupation of the right bank of the Rio Negro to confront them with the precautionary principle and the determinations of social and environmental sustainability of the Convention on Biological Diversity (CBD). Through a comparative study will be discussed in the following categories: Social organization of use of spaces in the cities of the Amazon, Environmental planning of regional development, environmental law and social and environmental sustainability. The research process consisted of four procedural moments (different, complementary, interdependent): bibliographic, documentary surveys, organizing and analyzing data and preparing the dissertation which was composed of three chapters. The first, characterized the problem space: the city of Iranduba, the second presents the Plan Occupation of the Right Bank of the Rio Negro. The third deals with the Brazilian Environmental Law and Sustainability.